A case report of twin pregnancy with complete hydatidiform mole following two frozen-embryos subsequent to ICSI (Intracytoplasmic Sperm Injection) - Morvarid Irani; Seyyedeh Adeleh Rahmanian; Malihe Mahmoodiniya; Marjaneh Farazestanian (Mashhad University of Medical Sciences, 2022)
Introduction: Intracytoplasmic sperm injection (ICSI) is an assisted reproductive technique for entering a sperm into the oocyte. In this study, a case of complete molar pregnancy which occurred following two frozen- embryo subsequent to ICSI was reported. Case report: The patient was a 36 years pregnant woman with 5 weeks' gestation following the transfer of two embryos who referred to Armaghan Infertility Center in Mashhad in January 2020 complaining of severe vaginal bleeding. The 6 weeks ultrasonography found two gestational sacs, one with viable fetus and one massive and empty. At this time, β-hCG value was 40,000 IU/ml. Therefore, twin pregnancy was identified. Spotting continued for two weeks. B-hCG value was >100,000 IU/ml and ultrasound showed molar pregnancy and missed abortion. Therefore, with diagnosis of twin pregnancy with complete hydatidiform mole, the patient underwent suction curettage. Histological examination confirmed the diagnosis of complete hydatidiform mole. Conclusion: Complete hydatidiform mole may happen after ICSI and this method cannot eliminate the incidence of molar pregnancy. Therefore, complete hydatidiform mole should be considered in pregnancy following ICSI which is associated with vaginal bleeding, large gestational sac and high serum β-hCG.